2015
DOI: 10.1117/1.jbo.20.12.127001
|View full text |Cite
|
Sign up to set email alerts
|

Miniature probe for the delivery and monitoring of a photopolymerizable material

Abstract: Abstract. Photopolymerization is a common method to cure materials initially in a liquid state, such as dental implants or bone or tissue fillers. Recent advances in the development of biocompatible gel-and cement-systems open up an avenue for in situ photopolymerization. For minimally invasive surgery, such procedures require miniaturized surgical endoscopic probes to activate and control photopolymerization in situ. We present a miniaturized light probe in which a photoactive material can be (1) mixed, press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…It was demonstrated that the addition of NFC reinforcements improves the hydrogel stiffness without compromising the failure strength or significant reduction of the water content. Moreover, the incorporated NFC fibers were shown to serve as a light-scattering source when the precursor solution is illuminated by UV light [22]. The latter accelerates the kinetics of photopolymerization and consequently allows reducing the required concentration of photoinitiator.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the addition of NFC reinforcements improves the hydrogel stiffness without compromising the failure strength or significant reduction of the water content. Moreover, the incorporated NFC fibers were shown to serve as a light-scattering source when the precursor solution is illuminated by UV light [22]. The latter accelerates the kinetics of photopolymerization and consequently allows reducing the required concentration of photoinitiator.…”
Section: Introductionmentioning
confidence: 99%
“…5c) by recording the reflected illumination spectra at different time points and by tracking the signal intensity over time. The intensity correlates directly with size of the photopolymerized hydrogel volume inside the tissue as previously shown [48]. Thus, if a known volume of hydrogel is injected, the signal intensity can be used to determine the time point of the full polymerization.…”
Section: Implantationmentioning
confidence: 71%
“…c) By recording the reflected illumination spectra a signal intensity is calculated. The intensity of the signal correlates with the amount of photopolymerized material and therefore provides valuable information about the reaction state of the implant in real time [48]. d) IVD during photopolymerization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, photoactivation can be triggered precisely by the operator by selectively switching the illumination module on. Moreover, it is theoretically possible to implement a feedback loop coupled to sound to monitor the solidification process by using light of a different wavelength through the same optical fiber (Schmocker et al, 2015).…”
Section: Discussionmentioning
confidence: 99%